Mapping and QTL Analysis of Gynoecy and Earliness in Bitter Gourd (Momordica charantia L.) Using Genotyping-by-Sequencing (GBS) Technology - Gangadhara Rao, P.; Behera, Tusar Kanti; Gaikwad, Ambika B.; Munshi, Anilabh Das; Jat, Gograj Singh; Boopalakrishnan, G. (Frontiers in Plant Science, 2018)
A high-density, high-resolution genetic map was constructed for bitter gourd (Momordica charantia L.). A total of 2013 high quality SNP markers binned to 20 linkage groups (LG) spanning a cumulative distance of 2329.2 cM were developed. Each LG ranging from 185.2 cM (LG-12) to 46.2 cM (LG-17) and average LG span of 116.46 cM. The number of SNP markers mapped in each LG varied from 23 markers in LG-20 to 146 markers in LG-1 with an average of 100.65 SNPs per LG. The average distance between markers was 1.16 cM across 20 LGs and average distance between the markers ranged from 0.70 (LG-4) to 2.92 (LG-20). A total of 22 QTLs for four traits (gynoecy, sex ratio, node and days at first female flower appearance) were identified and mapped on 20 LGs. The gynoecious (gy-1) locus is flanked by markers TP_54865 and TP_54890 on LG 12 at a distance of 3.04 cM to TP_54890 and the major QTLs identified for the earliness traits will be extremely useful in marker development and MAS for rapid development of various gynoecious lines with different genetic background of best combiner for development of early and high yielding hybrids in bitter gourd.